2021
DOI: 10.1016/j.cej.2020.127390
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microalgal biofilm formation and facilitated microalgae harvesting using a novel pH-responsive, crosslinked patterned and vibrating membrane

Abstract: Harvesting efficiency is one of the key issues restricting the further commercialization of microalgae. Traditional biofilm studies only tend to focus on enhancing biofilm formation, while neglecting the subsequent harvesting of the biofilm. In this study, a win-win strategy for high-density microalgal cultivation and low-cost harvesting through biofilm cultivation on a pH-responsive, charge-switchable, patterned membrane was investigated using a polyethylenimine (PEI)-crosslinked polyvinylidene fluoride (PVDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…As feedstocks for third-generation biofuels, microalgae exhibit advantages of a high photosynthetic efficiency, a high lipid content, and cost-effectiveness. Microalgal biodiesel has attracted immense interest because of its non-toxicity, biodegradability, and low pollution and emissions. , However, as the main components of biodiesel, fatty acid methyl esters (FAMEs) exhibit a high oxygen content, a long molecular chain (≥C 16 ), and poor low-temperature mobility. , Therefore, it is crucial to conduct subsequent deoxygenation (DO) and cracking processes to form jet fuel (C 8 –C 16 ) with better combustion performance, which is suitable for the aviation industry. , …”
Section: Introductionmentioning
confidence: 99%
“…As feedstocks for third-generation biofuels, microalgae exhibit advantages of a high photosynthetic efficiency, a high lipid content, and cost-effectiveness. Microalgal biodiesel has attracted immense interest because of its non-toxicity, biodegradability, and low pollution and emissions. , However, as the main components of biodiesel, fatty acid methyl esters (FAMEs) exhibit a high oxygen content, a long molecular chain (≥C 16 ), and poor low-temperature mobility. , Therefore, it is crucial to conduct subsequent deoxygenation (DO) and cracking processes to form jet fuel (C 8 –C 16 ) with better combustion performance, which is suitable for the aviation industry. , …”
Section: Introductionmentioning
confidence: 99%
“…Generally, harvesting microalga cultures is expensive, and biofilm-type culture methods are widely applied to address this problem; however, further research on aspects of its production, such as efficient harvesting and unit price reduction is required ( Witarsa et al, 2020 ; Zhao et al, 2021 ). Watari et al (2021) confirmed that mixing microalgae and bacteria in biofilm maximizes carbon absorption and biomass production, and reduces costs ( Wicker et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%